Attitude towards Spirituality and Spiritual Care among Nurses of Bharatpur Hospital - Malla, Shubhekshya; Ghimire, Anita (Journal of Nepal Health Research Council, 2024)
Background: Understanding spirituality and spiritual care is a prerequisite for holistic care in nursing. Spirituality is an important dimension of human existence with a crucial role in health promotion. The objective of this study was to assess the level of attitude towards spirituality and spiritual care among nurses. Methods: A cross-sectional analytical study design was used among 208 nurses to assess attitude toward spirituality and spiritual care among nurses of Bharatpur Hospital. A pretested semi-structured, self-administered questionnaire was used to collect data from the respondents. The instrument spirituality and spiritual care rating scales were used. Collected data were coded and entered in Microsoft office excel and SPSS version 22 was used for analysis. Results: The finding of the study revealed that, out of 208 respondents, the majority (74.0%) of respondents were of age 20-29 years with a mean and SD of 28.2±5.510. Among all, 125(60.1%) respondents had a moderate attitude score of 32-62, 83(39.9%) had a high level of attitude score of 63-92, whereas 0.5% had a low level of attitude towards spirituality and spiritual care score (0-31).There is no statistically significant relationship between the level of attitude and socio-demographic variables. Conclusions: It is concluded that most of the respondents had a moderate level of attitude. In-service education and awareness on providing spiritual care among nurses needs to be focused. Keywords: Attitude; holistic nursing; nurses; spirituality.